2005
DOI: 10.1109/tnn.2005.854369
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS Image Sensor With Programmable Pixel-Level Analog Processing

Abstract: A prototype of a 34 x 34 pixel image sensor, implementing real-time analog image processing, is presented. Edge detection, motion detection, image amplification, and dynamic-range boosting are executed at pixel level by means of a highly interconnected pixel architecture based on the absolute value of the difference among neighbor pixels. The analog operations are performed over a kernel of 3 x 3 pixels. The square pixel, consisting of 30 transistors, has a pitch of 35 microm with a fill-factor of 20%. The chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Intensive research on specialized high-speed analog vision chips with reduced supply power is observed. Confirmation of this fact can be found in the literature, where the analog vision chips [6][7][8][9][10][11][12][13][14][15][16] are faster and consume less power than the digital realizations [17][18]. The remainder of this paper is devoted to a general discussion, in Sec.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Intensive research on specialized high-speed analog vision chips with reduced supply power is observed. Confirmation of this fact can be found in the literature, where the analog vision chips [6][7][8][9][10][11][12][13][14][15][16] are faster and consume less power than the digital realizations [17][18]. The remainder of this paper is devoted to a general discussion, in Sec.…”
Section: Introductionmentioning
confidence: 56%
“…In this kind of matrix only simple vision processors occupying a small area can be used, otherwise the size of the entire array, and consequently the cost of its production will become excessively large. Examples of implementations of such systems in 0.35 µm CMOS technology are presented in [6,9,15], and [27][28][29][30][31].…”
Section: Architecture With An Embedded Array Of Processorsmentioning
confidence: 99%
“…between 5 and 10), it is possible to obtain images with high contrast, which can be efficiently binarized. Even though technical details on the vision sensor and its operating modes are reported in [1], it is worth to shortly describe how the sensor extracts the spatial edge, which is used for the presented application. Sensor embedded edge extraction is executed accumulating the absolute value of the pixel difference, as described in eq.…”
Section: Iichip Descriptionmentioning
confidence: 99%
“…Several solutions have been proposed both at system and chip level using different approaches: correlation [2], block matching [3], gray-level tracking [4]. Different approaches have been proposed in the last decades to determine the motion vector [1,7]. Some [10,11] use a linear array, executing template matching between the reference and the current frames.…”
Section: Iintroductionmentioning
confidence: 99%
“…The vision sensors are constructed using p-n diodes or transistors exposed to light, which convert light to an electrical signal. A relatively small photo-current in the pA range, generated by the photo-sensors, can be converted to voltage with an amplitude of about 1 V in order to allow processing in the voltage-mode analogue processors [10][11][12][13][14][15][16][17]. Another approach is to directly amplify the photo-current to the µA level, in order to be processed in the current-mode analogue processors [5][6][18][19].…”
Section: Introductionmentioning
confidence: 99%